Evaluation of the clinical application of information-motivation-behavior model care combined with labetalol pharmacotherapy for patients with hypertensive disorders of pregnancy: a randomized controlled study for improving pregnancy outcomes - Sun, Linling; Chen, Jiamei (Frontiers in Medicine, 2025)
BackgroundThe aim of this study was to assess the effect of Information-Motivation-Behavioral Model of Care (IMB) combined with labetalol medication on pregnancy outcomes in patients with hypertensive disorders of pregnancy (HDP).MethodsThe study was a randomised, single-blind clinical trial with 130 patients with HDP admitted between February 2021 and February 2025, who were randomly assigned to the control and intervention groups. The control group received conventional labetalol medication, whereas the intervention group received a nursing intervention based on the IMB model. The IMB care consisted of the establishment of a dedicated nursing intervention team, informational interventions (e.g., health education), motivational interventions (e.g., personalised dietary life plan development), and behavioral interventions (e.g., guidance on self-monitoring of blood pressure).ResultsIMB care combined with labetalol significantly increased patients’ self-efficacy, improved blood pressure control, and provided relief from negative emotions compared with labetalol alone. In addition, the intervention group had a longer gestational week of delivery (p = 0.04), less chance of vaginal delivery to caesarean section (p = 0.048), and a trend towards a decrease in the incidence of adverse pregnancy outcomes such as preterm labor and adverse effects such as nausea, albeit not statistically significant (p > 0.05).ConclusionThe IMB care model combined with labetalol medication had a positive impact on blood pressure control and pregnancy outcomes in patients with HDP, providing data support and theoretical basis for the application of this care model in HDP. However, the study also pointed out its limitations, such as single-centre design and limited sample size, and more comprehensive studies are needed to further validate these findings in the future.